Outcome of Lateral Internal Sphincterotomy in Terms of Frequency of Pain and Wound Healing in The Treatment of Anal Fissure - Mohsin, Wajiha; Ijaz, Abeer; Nadeem, Marriyam (Indus Journal of Bioscience Research, 2025)
Introduction: Anal fissure is a common anorectal condition causing severe pain and bleeding during defecation. Lateral internal sphincterotomy (LIS) is a widely used surgical treatment aimed at relieving pain and promoting wound healing. This study evaluated the outcome of closed LIS in terms of post-operative pain and wound healing. Methodology: This descriptive case series was conducted at the Department of General Surgery, Fatima Memorial Hospital, Lahore, over six months. A total of 100 patients aged 20 to 55 years with clinically diagnosed anal fissure underwent closed lateral internal sphincterotomy. Post-operative pain was assessed using the Visual Analogue Scale (VAS) at 24 hours, while wound healing was evaluated after four weeks. Data were analyzed using SPSS version 25, and p-values ≤ 0.05 were considered statistically significant. Results: Out of 100 patients, 56% were male and 44% female. The mean age was 38.29 ± 10.74 years, and the mean BMI was 24.89 ± 3.17 kg/m². Post-operative pain was reported by 18% of patients, with a mean VAS score of 2.36 ± 1.25. Wound healing was achieved in 83% of cases. Conclusion: Closed lateral internal sphincterotomy is an effective procedure for treating anal fissure, with a high wound healing rate and minimal post-operative pain.